SPECIFIC EXERCISE TARGETING THE SEMITENDINOSUS IN FEMALE ACL-RECONSTRUCTED ATHLETES. Issue 7 (11th March 2014) - Lauridsen, HB; Bencke, J; Thorborg, K; Andersen, LL; Sonne-Holm, S; Aagaard, P; Hölmich, P; Zebis, MK
Abstract : Background: The most commonly used graft in ACL-reconstructions is harvested from the semitendinosus muscle (ST) which causes atrophy and reduced muscle strength in the hamstrings. As the ST serves as an important ACL agonist, exercises that causes high levels of ST muscle activity after ACL-reconstruction, is of great interest to prevent re-rupture of the ACL. Objectives: The purpose of the present study was to examine the level of neuromuscular hamstring muscle activity during two commonly used strength exercises, the two hand Kettlebell Swing (KS) and the Nordic Hamstring (NH), in previously ACL-reconstructed female athletes. Design: Cross-sectional study. Settings: Biomechanical laboratory. Participants: Recruitment ongoing – the study is planned to include 20 participants. Preliminary data from five female athletes (age 28±7 yrs) with a total of 6 ACL-reconstructed knees are presented. In all cases, ST tendon was used as graft. The time between surgery and testing was 52±47months. Intervention: Ten consecutive KS's were performed corresponding to a maximal load (12–16 kg) where correct technique was maintained. Additional, five consecutive NH curls were executed. Muscle activity for the hamstring muscles was obtained during the exercise evaluation and during hamstring MVC. Main outcome measurements: Peak EMG of the medial (ST) and lateral (BF) hamstring during KS and NH was normalized to peak EMG amplitude during MVC. Results: The exercise evaluation showed a significantly higher peak ST EMG activity during KS than NH (91±23% vs. 63±23%, respectively), P=.011. No difference was observed in peak BF EMG activity between exercises (82±30% vs. 66±36%, respectively), P=.125. Conclusion: The present finding suggests that the KB exercise could be introduced in rehabilitation when aiming at enhanced ability to recruit ST during forceful movements. However, to avoid adverse effects in the early phase of rehabilitation, caution must be taken when introducing high-intensity training among ACL reconstructed patients.